To Evaluate the Effect of Structured Training Program about Premenstrual Syndrome on the Knowledge and Perception of Nursing Students at a Government Nursing Teaching Institute in Northern India - Latika; Namita Batra; Pushpa Dahiya (Journal of Applied Sciences and Clinical Practice)
Background: Premenstrual syndrome (PMS) encompasses a range of symptoms that manifest in individuals between menstruation and ovulation. The prevalence of PMS will be lower among students with sufficient knowledge about PMS than among those without such information. Objective: The purpose of this study was to assess nursing students’ knowledge and perception on PMS. Furthermore, the study aimed to determine if structured training interventions were effective in enhancing the students’ initial knowledge and perception levels. Materials and Methods: This study was conducted on nursing students from Govt. Nursing College, using a single-group pre–post interventional design. A pretested questionnaire was utilized as the research instrument. The intervention in the form of structured training program was imparted to the participants. Results: The pretest group exhibited a lower mean knowledge score (M = 25.0000, standard deviation (SD) =8.26225, standard error (SE) =0.55704) than the posttest group (M = 29.4773, SD = 9.64315, SE = 0.65014). A noteworthy difference was observed in the mean knowledge scores (t = −7.590085, P = 0.00001). The pretest group exhibited a lower mean perception score (M = 34.7591, SD = 3.55404, SE = 0.23961) than the posttest group (M = 36.2182, SD = 3.96533, SE = 0.26734). There were significant differences in perception scores, as evidenced by the statistical analysis (t = −6.244328, P = 0.00001). Conclusions: The results showed that the educational intervention led to significant improvements in their knowledge and perceptions about PMS.